Let $(\mathcal{H}, (\cdot, \cdot))$ be a complex Hilbert space, and $A : \mathcal{H} \to \mathcal{H}$ a positive, bounded operator ($A$ being positive means $(Ax,x) \ge 0$ for all $x \in \mathcal{H}$).

Prove that $A$ is self-adjoint. That is, prove that $(Ax,y) = (x, Ay)$ for all $x,y \in \mathcal{H}$.

Here's what I have so far. Because $A$ is positive we have $\mathbb{R} \ni (Ax,x) = \overline{(x,Ax)} = (x,Ax)$, all $x \in \mathcal{H}$.

Next, I have seen some hints that tell me to apply the polarization identity:

$$(x,y) = \frac{1}{4}((||x+y||^2 + ||x-y||^2) - i(||x + iy||^2 - ||x - iy||^2)),$$

where of course the norm is defined by $|| \cdot||^2 = (\cdot, \cdot)$. So my guess is that I need to start with the expressions:

$$(Ax,y) = \frac{1}{4}((||Ax+y||^2 + ||Ax-y||^2) - i(||Ax + iy||^2 - ||Ax - iy||^2)),$$

$$(x,Ay) = \frac{1}{4}((||x+Ay||^2 + ||x-Ay||^2) - i(||x + iAy||^2 - ||x - iAy||^2)),$$

and somehow show they are equal. But here is where I have gotten stuck.

Hints or solutions are greatly appreciated.


You should apply the polarization identity in the form

$$4(Ax,y) = (A(x+y),x+y) - (A(x-y),x-y) -i(A(x+iy),x+iy) + i(A(x-iy),x-iy).$$

Since you already know $(Az,z) = (z,Az)$ for all $z \in \mathcal{H}$, it is not difficult to deduce $A^\ast = A$ from that.

  • $\begingroup$ Consider the operator on 2D Hilbert space given by the matrix $A = \left[\begin{matrix}1&1\\-1&1\end{matrix}\right]$. Isn't this positive, but not self-adjoint? What am I missing? $\endgroup$ – Stephen Montgomery-Smith Nov 10 '13 at 22:14
  • $\begingroup$ $(Ax,x) = 2(1+i)$ isn't real for $x = (1,i)$. $\endgroup$ – Daniel Fischer Nov 10 '13 at 22:18
  • $\begingroup$ Yes, I just realized that 10 seconds before your post! $\endgroup$ – Stephen Montgomery-Smith Nov 10 '13 at 22:19
  • $\begingroup$ Thank you for the answer. Should we have a minus sign in front of the term $(A(x-y), x-y)$? $\endgroup$ – JZS Nov 10 '13 at 23:04
  • 1
    $\begingroup$ Can you give a hint of how this form of the polarization identity is derived? This is not the usual form that I have seen, which is just $(x,y)=\frac{1}{4}\sum_{k=0}^3 i^k \| x + i^k y\|$ $\endgroup$ – Squirtle Dec 10 '18 at 0:05

Another solution is this one:

$T$ is self-adjoint iff $\langle Tx,x\rangle \in \mathbb{R}$ for every $x\in \mathcal{H}$.

Let $x\in \mathcal{H}$. Then $0=\langle Tx,x \rangle-\langle T^{*}x,x \rangle = \langle Tx,x \rangle-\overline{\langle Tx,x \rangle}=2i\operatorname{Im}\langle Tx,x\rangle \iff \langle Tx,x \rangle \in \mathbb{R}$. Thus $T=T^{*} \iff \langle Tx,x\rangle \in \mathbb{R}$ for every $x\in \mathcal{H}$.

Because $T$ is positive we have that $\langle Tx,x \rangle \in \mathbb{R}$.

  • $\begingroup$ @jtms88 ,check my proof please.thank you $\endgroup$ – Haha Nov 24 '13 at 12:53
  • 3
    $\begingroup$ It isn't complete since you cannot conclude that $T=T^*$ from $\langle Tx,x\rangle=\langle T^*x,x\rangle$. You still need to use an argument similar to the one given by Daniel Fischer to deduce it. $\endgroup$ – Lolman Jul 24 '18 at 16:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.